Analisis Risiko Produksi Olahan Stroberi pada PT Strawberry Corps Indonesia di Desa Pancasari: Analisis Risiko Produksi Olahan Stroberi pada PT Strawberry Corps Indonesia di Desa Pancasari - WIGUNA, I GEDE ADI INDRA; DEWI, NI LUH PRIMA KEMALA (Universitas Duta Bangsa Surakarta, 2025)
PT Strawberry Corps Indonesia is one of the micro-scale MSMEs that has been incorporated as an Individual Company (PT). This research raises several issues, namely what are the risks that have the potential to arise, how to assess the level of risk, and what is the right mitigation strategy to deal with risks. This research aims to identify and determine potential risks, assess priority risks, and provide appropriate mitigation plans to overcome the risks contained in PT Strawberry Corps Indonesia. The method used is the Failure Mode and Effect Analisys (FMEA) method. There are 16 risk events contained in all stages of strawberry processed production activities. The highest risk falls into the Intolerable category with an RPN value of 448, and the lowest risk falls into the Broadly Acceptable category with an RPN value of 6. There are several risk mitigation plans related to the cause of the risk, namely: facilitating farmers to get education through cooperation with PPL and the Agriculture Office, coordinating or contracting with suppliers, recruiting part-time labor, maintaining the quality of raw materials by setting quality standards for raw materials, storing raw materials at a temperature of - 18°C and conducting routine checks on the cleanliness of equipment and production rooms before production.